FAECAL CONTINENCE AFTER RECONSTRUCTION OF ANORECTAL MALFORMATIONS - Polona Studen Pauletič (The Society for Children with Metabolic Disorders, 2020)
The aim of the article is to review anorectal malformations. Babies born with anorectal anomalies need surgical treatment to be able to pass meconium and faeces. Surgical management can sometimes be achieved in a single stage. A two-stage procedure is required for more complex anomalies, with the ﬁrst stage being the formation of a diverting colostomy. Children born with less complex anorectal malformations have a better prognosis for faecal continence, but, unfortunately, also a higher tendency for constipation. Those with more complex anomalies have poorer muscle development, altered intestinal motility and sensation, and a worse prognosis for complete faecal continence. It is of great importance to prevent constipation after surgical reconstruction. The aim of bowel management is to achieve regular bowel movement with dietary adjustments and laxatives if needed. In faecal incontinence, regular enemas can be used. They must be tailored to each patient. Iatrogenic faecal incontinence is a rare postoperative complication.